Integrated Management of South American Tomato Leaf Miner [Tuta Absoluta (Meyrick)]: A Review - Joshi, Arati; Thapa, Resham B.; Kalauni, Dharmendra (Journal of the Plant Protection Society, 2018)
Tuta absoluta (Meyrick) is one of the newly introduced insect pest of tomato in Nepal, which was first detected by Entomology Division, Nepal Agricultural Research Council from a commercial tomato grower of Balaju, Kathmandu on 16th May 2016. The pest occurs all-round the year within the temperature range of 20-27° C, and therefore, the environment of mid hills and plains of Nepal is suitable for sustaining the pest except during the winter season. T. absoluta pest mainly attacks Solanaceous crops, especially evident in tomato, however, it is also found in non-solanaceous crops. Larva of the pest is devastating causing damage in fruit, leaves and stem, and reducing tomato production by 80-100% in open field as well as in plastic house, if no control measures are carried out. Chemicals, like Spinosad, Chlorantraniliprole and Novaluron are recommended in Nepal for controlling this pest, but studies have revealed the inefficacy of chemical control measures due to wide host range, faster reproducing ability and development of pesticide resistance. Therefore, Integrated Pest Management (IPM) with mass trapping of the pest using pheromone trap, biological control by predator, parasitoid, entomopathogenic microbes, including cultural practices are imperative for the effective control of this pest.